The JHSF case: how the company's unique business model set it on an unprecedented growth trajectory during the COVID-19 pandemic - Cury, Marcelo Liguori (2024)
Despite the profound impact of the COVID-19 pandemic on Brazil's population and economy, some companies were able to grow considerably during the same period. One such company was JHSF (JHSF3), a real estate development and management company, which grew its revenues by 227% in 2 years. This thesis aims to understand the company's business model and to describe the transformation it went through, arguing that its choice of focusing solely on the high-income segment while keeping a fairly diverse portfolio was a key element for the company to achieve such remarkable figures. Through comparative analysis with industry peers, such as Iguatemi and Cyrela, the study highlights how JHSF's unique positioning was key for the company to be able to outgrow its competitors and the sectors it operates in. However, it's important to note that this analysis solely identifies a correlation between these variables rather than establishing a causal relationship.